2006
DOI: 10.1523/jneurosci.5216-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Overexpressing Glycogen Synthase Kinase 3β: A Putative Model of Hyperactivity and Mania

Abstract: Lithium is used as treatment for bipolar disorder with particular efficacy in the treatment of mania. Lithium inhibits glycogen synthase kinase 3␤ (GSK-3␤) directly or indirectly via stimulation of the kinase Akt-1. We therefore investigated the possibility that transgenic mice overexpressing GSK-3␤ could be of relevance to model bipolar disorder. Transgenic mice showed hypophagia, an increased general locomotor activity, and decreased habituation as assessed in an open field, an increased acoustic startle res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
246
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(259 citation statements)
references
References 60 publications
10
246
1
2
Order By: Relevance
“…It was reported that transgenic mice overexpressing GSK3b recapitulate hyperactivity as observed in the manic phase of bipolar disorder. 99 Our result suggests that the decreased GM05926 GM05932 GM05988 GM05990 GM06028 GM06024 GM05984 GM05915 GM05897 pGSK3β (S9)…”
Section: Discussionmentioning
confidence: 66%
“…It was reported that transgenic mice overexpressing GSK3b recapitulate hyperactivity as observed in the manic phase of bipolar disorder. 99 Our result suggests that the decreased GM05926 GM05932 GM05988 GM05990 GM06028 GM06024 GM05984 GM05915 GM05897 pGSK3β (S9)…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, transgenic mice overexpressing the circadian modulator, GSK3β, are hyperactive, have reduced immobility in the forced swim test (indicative of lower depression-like behavior), and an increased startle response (Prickaerts et al, 2006). These behaviors are reminiscent of bipolar patients in the manic state.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…Single-nucleotide polymorphism analysis and studies with animal models that have disrupted circadian rhythms have indicated a molecular link between circadian rhythms and mood regulation (Curtis et al, 2007;McClung, 2007;Prickaerts et al, 2006;Roybal et al, 2007). Our findings here indicate that PK2, as an SCN circadian output factor, also plays a critical role in the regulation of stress-related traits.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, mice harboring a mutation in the Clock gene were shown to display reduced depression-like behavior in the forced swimming and learned helplessness tests, as well as reduced anxiety or increased risk-taking behavior in several measures (Easton et al, 2003;Roybal et al, 2007). Transgenic mice overexpressing GSK3b, a circadian modulator, are hyperactive and have reduced immobility in the forced swimming test, indicating lower depression-like behavior (Prickaerts et al, 2006). Thus, these studies have implicated the link between mood regulation and certain circadian genes.…”
Section: Introductionmentioning
confidence: 95%